2019
DOI: 10.2147/cia.s197146
|View full text |Cite
|
Sign up to set email alerts
|

<p>Risk factors of ventilator-associated pneumonia in elderly patients receiving mechanical ventilation</p>

Abstract: Purpose: The aim of this study was to verify the potential risk factors of ventilator-associated pneumonia (VAP) in elderly Chinese patients receiving mechanical ventilation (MV). The secondary aim of this study was to present logistical regression prediction models of VAP occurrence in elderly Chinese patients receiving MV. Methods: Patients (aged 80 years or above) receiving MV for ≥48 h were enrolled from the Chinese People’s Liberation Army (PLA) General Hospital from Jan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 59 publications
0
22
0
3
Order By: Relevance
“…Accumulating results verified that the use of ventilator and arteriovenous catheterization was associated with an invasive medical device or invasive procedure, which are independent risk factors for nosocomial bacteria infection. 20,25 The results of this study showed that the probability of nosocomial bacteria infection increased in patients using a ventilator. Intravenous catheterization can lead to colonization as well as a broad spectrum of infections ranging from catheter site infections to catheter-related blood stream infections.…”
Section: Discussionmentioning
confidence: 76%
“…Accumulating results verified that the use of ventilator and arteriovenous catheterization was associated with an invasive medical device or invasive procedure, which are independent risk factors for nosocomial bacteria infection. 20,25 The results of this study showed that the probability of nosocomial bacteria infection increased in patients using a ventilator. Intravenous catheterization can lead to colonization as well as a broad spectrum of infections ranging from catheter site infections to catheter-related blood stream infections.…”
Section: Discussionmentioning
confidence: 76%
“…DM or previous chronic pulmonary disease did not predispose to pneumonia in the present study. Although studies of OI and pneumonia remain scarce, in different OI settings both DM and COPD have been identified as significant risk factors for nosocomial pulmonary infections, and patients with DM have been shown to have different and rarer bacterial strains and a significantly higher drug resistance rate than patients without DM [28][29][30][31]. In large cohorts, the pneumonia risk in DM patients seems obvious; López-de-Andrés et al [32] reported a 21% higher incidence of postoperative pneumonia in DM patients than in non-diabetic patients in a cohort of over 100,000 patients, although contradictory results have also been reported [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…For some patients who needed catheter insertion, such as nasal catheter, mask, tracheal intubation and so on, bacteria easily entered the body through the catheter cavity and lead to catheter-related infection finally. The untimely treatment of such infection often resulted in death [ 12 ]. Based on this background, we studied the effects of EAT on 30-day mortality and hospital length of stay.…”
Section: Introductionmentioning
confidence: 99%